Firm-specific, macroeconomic variables and REIT returns: empirical evidence from Singapore exchange - Dana, Chomanova (2018)
Publicly traded REITs offer investors high return, receive special tax treatment and provide a highly liquid method of investing in real estate. REITs have been a popular financial investment tool in Singapore. With their emphasis on income-generating assets, REITs are better able to attract capital seeking property exposure, thereby freeing capital that can be better invested other areas to expand businesses and invest in new ventures. Therefore, it is important to define which fundamental variables are related to REIT’s return. Panel data analysis fixed effect model is used to examine the sensitivities of annualised S-REIT returns from 2011 – 2016 towards a set of five firm-specific variables and two market-wide risk variables. In particular, we examine the time-varying and cross-sectional differences between the impacts of firm size, the degree of leverage, book-to-market ratios, NAV, EPU and international diversification. Our regression results find that the size effect and leverage have had a negative impact of returns. Our findings on the relationship between book-to-market ratios and SREIT returns show that the market places a premium on SREITs with higher book-to-market ratios. Additionally, the results show that changes in interest rate and international diversification strategy have an insignificant effect on S-REIT return.